Una verdad incómoda - Marquina, Orietta (2009)
The video An Unconvenient Truth (Guggenheim 2006) is analysed at the light ofthe sustainable development theories: It works as starting point for some reflections about the sense and practice of education in relation with the Global Warming phenomenon. What we need today is an education that disturbs our habits and customs,the manner we relate to nature and our expectations and concept on welfare.Bothering us and bothering others, education will friendly accommodate our life,both material and spiritual, to environment in a sustainable manner. We need an education that helps us to create new collective imaginaries to guide our daily action,both individual and in community, building new roads to sustainable development.